A Realist Evaluation of a Recovery-Oriented Inpatient Service - Amy Pritchard (2021)
Background: Finding effective means of supporting individuals with a mental illness in their recovery is essential. A new recovery-oriented inpatient service in South Wales, “Woodlands”, aimed to provide an environment that would support individuals with severe and enduring mental illness in their recovery. Woodlands focuses on providing a staffing group that were recovery-oriented and deliver high levels of therapeutic engagement, as well as promoting choice and responsibility to develop service-users’ skills and confidence for living in the community in the future. This thesis aimed to explain which parts of Woodlands worked, for whom and in what circumstances.Design: Three areas of Woodlands’ service delivery were evaluated. This included - Woodlands trying to establish itself as a new service, how the staffing model supported individuals in their recovery, and how service-user choice and responsibility was promoted and supported by the service. Realist evaluation and ecological systems theory were used to guide the analysis of multiple data strands. This included quantitative data routinely collected at Woodlands and qualitative research interviews. The qualitative research interviews were conducted with senior figures involved in the design of the service, staff members, service-users and commissioners who were involved in referring individuals to Woodlands.Findings: The findings of this study are multifaceted and focus on the conditions of successful or unsuccessful implementation and delivery of a new recovery-oriented inpatient service. Such conditions included there being a market demand for this type of service and having the ability to quantifiably evidence the effectiveness of the service in order to secure referrals. Several service-user and staff characteristics were identified as conditions for the successful or unsuccessful engagement with key resources at Woodlands. These individual-level conditions included service-users and staff having the confidence, skills and desire to engage or deliver these resources. The congruence model (Nadler & Tushman, 1980) was used to provide explanatory power to the findings of this thesis, focusing specifically upon Woodlands challenge of establishing itself as a provider. The findings highlight that the four facets of organisational effectiveness (the people, tasks, culture and structure), were not congruent with the service’s inputs, nor were they congruent when the service was forced to adapt its service-user criterion.Discussion: The findings are presented in a nuanced middle-range theory which uses the underpinnings of the congruence model (Nadler & Tushman, 1980). The nuanced theory captures the challenges of establishing a new mental health service, which has translatability for other services trying to establish themselves within the competitive and commercial arena of healthcare. The findings of this thesis raise the question of whether recovery-oriented care can ever truly be achieved within the confines of inpatient care and it is argued that perhaps what services are really doing is a form of contemporary rehabilitation but dressed up in the clothes of recovery.